2018
DOI: 10.1140/epje/i2018-11682-y
|View full text |Cite
|
Sign up to set email alerts
|

Rotating flow of Ag-CuO/H2O hybrid nanofluid with radiation and partial slip boundary effects

Abstract: The main object of the present paper is to examine and compare the improvement of flow and heat transfer characteristics between a rotating nanofluid and a newly discovered hybrid nanofluid in the presence of velocity slip and thermal slip. The influence of thermal radiation is also included in the present study. The system after applying the similarity transformations is solved numerically by using the bvp-4c scheme. Additionally, numerical calculations for the coefficient of skin friction and local Nusselt n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
85
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(87 citation statements)
references
References 40 publications
2
85
0
Order By: Relevance
“…In the same year, the 3D magnetohydrodynamics MHD flow of hybrid nanofluid was considered by Devi and Devi [24], and their numerical results coincided with the experimental results obtained by Suresh et al [15]. Because of these encouraging findings, the newly found thermophysical properties have been considered by many researchers in their studies, such as Das et al [25], Mehryan et al [26], Chamkha et al [27], Hayat et al [28], Saba et al [29], Kumar and Sarkar [30], Kassai [31], and Ghalambaz et al [32]. Recently, Waini et al [33] considered the unsteady flow of hybrid nanofluid, by mixing copper and alumina (nanoparticles) with water (base fluid).…”
Section: Introductionmentioning
confidence: 56%
“…In the same year, the 3D magnetohydrodynamics MHD flow of hybrid nanofluid was considered by Devi and Devi [24], and their numerical results coincided with the experimental results obtained by Suresh et al [15]. Because of these encouraging findings, the newly found thermophysical properties have been considered by many researchers in their studies, such as Das et al [25], Mehryan et al [26], Chamkha et al [27], Hayat et al [28], Saba et al [29], Kumar and Sarkar [30], Kassai [31], and Ghalambaz et al [32]. Recently, Waini et al [33] considered the unsteady flow of hybrid nanofluid, by mixing copper and alumina (nanoparticles) with water (base fluid).…”
Section: Introductionmentioning
confidence: 56%
“…Meanwhile, Moghadassi et al [20] studied the Al 2 O 3 − Cu/ water base hybrid nanofluid numerically and found that "for the hybrid nanofluids, the average Nusselt number increase was 4.73% and 13.46% in compared to Al 2 O 3 water and pure water, respectively". Moreover, this model has been widely employed by many researchers, such as Hayat et al [21], Saba et al [22], Acharya et al [23], Afridi et al [24], Shafiq et al [25,26], and Manh et al [27]. Furthermore, Khashi'ie et al [28] found dual solutions of magnetohydrodynamic (MHD) flow of a hybrid nanofluid in the presence of Joule heating and noticed that higher values of Eckert number do not affect boundary layer separation.…”
Section: Introductionmentioning
confidence: 99%
“…Different combinations of nanoparticles and base fluid were also considered, i.e. MgO-MWCNT/ethylene glycol by Soltani and Akbari (2016), MgO-MWCNTs/EG by Vafaei et al (2017), TiO 2 -Cu/H 2 O by Ghadikolaei et al (2017), Ag-CuO/water by Hayat and Nadeem (2017) and Hayat et al (2018), Cu-Ag/water by Hassan et al (2018b), Ag-MgO/water by Ghalambaz et al (2019) and graphene-platinum hybrid nanofluids by Bahiraei and Mazaheri (2018), respectively. Devi and Devi (2016a) and Devi (2017, 2016b) investigated on the boundary layer flow of hybrid Cu-Al 2 O 3 /water nanofluid numerically due to a stretching sheet.…”
Section: Introductionmentioning
confidence: 99%
“…Devi and Devi (2016a) and Devi (2017, 2016b) investigated on the boundary layer flow of hybrid Cu-Al 2 O 3 /water nanofluid numerically due to a stretching sheet. Nadeem et al (2018) explored the stagnation point flow of hybrid Cu-Al 2 O 3 / water nanofluid on a circular cylinder while Rostami et al (2018) Marangoni convection is generated due to the variations of surface tension gradients, either in the temperature, concentration or both gradients. Marangoni convection is extensively applied in welding (Bachmann et al 2016;Cui et al 2018;Kidess et al 2016), crystal growth (Minakuchi et al 2017;Timoveef et al 2015) and soap film stabilisation (Bournival et al 2017;Raza et al 2016).…”
Section: Introductionmentioning
confidence: 99%